Development of insulated Cu wire ball bonding - Leong H.Y.; Mohd F.Z.; Ibrahim M.R.; Kid W.B.; Khan N.; Kar Y.B.; Tan L.C. (2023)
Insulated Cu wire is the next generation technology in fine pitch and high density wire bonding, which enables wire crossing and touching without concern for wire-to-wire shorts. However, insulated Cu wire bonding is still at the infant stage compared to Cu wire bonding. This study investigates the wire bond process in term of free air ball (FAB) and ball formation using 20?m Cu wire and insulated Cu wire with target bonded ball size about 35?m. Insulated Cu wire needs a different set of EFO setting compared to Cu wire. Spherical and residue free FAB of insulated Cu was able to form with forming gas. With a set electric flame off (EFO) setting, insulated Cu FAB consistently larger than Cu FAB. The experimental results show clearly that the energy required for the FAB formation for insulated Cu wire is ?20% lower than the Cu wire, probably due to the lesser heat loss from the wire during the EFO firing. Key bonding parameters for insulated Cu were EFO current, EFO time, bond power and bond force to meet the required ball size. This study shows that insulated Cu wire requires less demanding ball bond parameters than Cu wire, indicating softer ball which could be favorable for the sensitive bond structures. Bonding strength in term of ball shear and wire pull strength between the insulated Cu wire and Cu wire is very similar. Other key responses such as Al remnant, pad cratering and intermetallic compound have been studied and will be discussed in details in the paper. Our research successfully established good wire bonding process conditions for the insulated Cu wire and subsequently demonstrated that the technology is feasible using presently available wire bonder. 2012 IEEE.